1986
DOI: 10.1002/ajpa.1330690308
|View full text |Cite
|
Sign up to set email alerts
|

Architectural and histochemical diversity within the quadriceps femoris of the brown lemur (Lemur fulvus)

Abstract: Physiologically related features of muscle morphology are considered with regard to functional adaptation for locomotor and postural behavior in the brown lemur (Lemur fulvus). Reduced physiological cross-sectional area, estimated maximum excursion of the tendon of insertion, length of tendon per muscle fasciculus, and areal fiber type composition were examined in the quadriceps femoris in order to assess the extent of a "division of labor" among four apparent synergists. Each of these four muscles in this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…These authors, relying on fibre-type data from other prosimians [41], speculated on the fibre content of various heads of the lemur quadriceps femoris. The speculations were subsequently confirmed histochemically by Anapol and Jungers [19], who found that vastus intermedius was 82% type I fibres whereas all the other heads were greater than 90% type II fibres.…”
Section: Figmentioning
confidence: 49%
See 2 more Smart Citations
“…These authors, relying on fibre-type data from other prosimians [41], speculated on the fibre content of various heads of the lemur quadriceps femoris. The speculations were subsequently confirmed histochemically by Anapol and Jungers [19], who found that vastus intermedius was 82% type I fibres whereas all the other heads were greater than 90% type II fibres.…”
Section: Figmentioning
confidence: 49%
“…Armstrong et al [78] found a 'small but consistent' trend along these lines in three heterogeneous muscles of the dog. Such was also found to be the case for the heads of the quadriceps femoris in Eulemur fulvus [19], the human soleus and vastus lateralis [31], and the equine gluteus medius [14,35]. Burke [4] was also quick to point out that type I fibres of the homogeneous cat soleus are about the same size as the large type IIb fibres of that animal's gastrocnemius.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, much less literature is available for chimpanzees, and no study of ape muscle function has directly measured muscle PCSAs or the moment arms of the muscles about the joints [although note that Anapol and Jungers (1986) and Babcock (1994) have published data for lemurs and galagos, respectively, and Yamazaki (1985) made single estimates of the moment arms of some chimpanzee muscles]. Doran (1992a,b) and Hunt (1994) have published extensive data on the frequencies of the different locomotor modes exhibited by free ranging chimpanzees, and Hunt (1990Hunt ( , 1992Hunt ( , 1994 in particular has attempted to relate morphological characteristics of the appendicular skeleton of chimpanzees to behaviour and ecology.…”
mentioning
confidence: 99%
“…In contrast, small species with the ability for fast movement have a high proportion of fibres of fast contraction speed in most of their muscles (Ariano et al, 1973;Sickles and Pinkstaff, 1981a;Jouffroy et al, 2003). Studies in primates have shown that the population of the fibre type in the muscle varies according to the predominant way of locomotion of each species (Ariano et al, 1973;Plaghki et al, 1981;Sickles and Pinkstaff, 1981a, b;Moriyama, 1983;Anapol and Jungers, 1986;Petter and Jouffroy, 1993;Jouffroy et al, 1999).…”
Section: Introductionmentioning
confidence: 99%